New pollen evidence from Nariani (Georgia) for delayed postglacial forest expansion in the South Caucasus. Issue 1 (6th February 2017) - Messager, Erwan; Nomade, Sébastien; Wilhelm, Bruno; Joannin, Sébastien; Scao, Vincent; Von Grafenstein, Ulrich; Martkoplishvili, Inga; Ollivier, Vincent; Mgeladze, Ana; Dumoulin, Jean-Pascal; Mazuy, Arnaud; Belmecheri, Soumaya; et al.
Abstract: The nature and timing of environmental changes throughout the last glacial-interglacial transition in the South Caucasus, and more widely in eastern Europe, are still not fully understood. According to certain pollen records, forest expansion occurred in many areas several millennia after what is considered worldwide as the onset of the Holocene. The current problem we face is that the time lag in forest expansion varies from one sequence to another, sometimes with no delay at all. Moreover, the potential forcing/controlling factors behind this complex pattern, contrary to the almost synchronous global Holocene warming, are still a matter for debate. Accordingly, we revisit the issue of forest expansion through vegetation history obtained in the South Caucasus using a new pollen record, retrieved from the Nariani paleolake (South Georgia). These data attest to a steppic phase, initially dominated by Amaranthaceae-Chenopodiaceae (12, 700–10, 500 cal yr BP), then by Poaceae (10, 500–9000 cal yr BP), culminating with a more forested phase (9000–5000 calyrBP). Although some palaeoclimatic regional reconstructions show a wet early Holocene, we interpret the delay in forest expansion recorded in Nariani (2500 years) as the result of reduced spring precipitation, which would have limited forest development at that time.